المصلح الشيخ عمار بن الأزعر وجهوده في التحرير والتنوير بالديار السوفية - عثماني, الجباري (جامعة الوادي - University of Eloued, 2019)
In the late 19th century and the early 20th century, the Oued Souf region witnessed a scientific migration of Soufian characters from many villages and towns towards the El Zaytouna Mosque in Tunis. Most of them returned with the forensic and mental sciences, imbued with reformist liberal thought and freed from the limits of subordination to the Sheikh and the ruling regime. From this group of righteousness, the star of the world, Ammar ibn al-Azar, was brightened. The article deals with the reform, education and enlightenment activity of this world in the first half of the twentieth century, and the suffering it suffered.
مقال
Keywords: الوادي؛ الإزعر؛ سوف؛ التنوبر